Tripod-Fix device for the treatment of painful osteoporotic vertebral compression fractures - Hsiang-Yi Hung; Shin-Yuan Chen (Scientific Reports, 2024)
Abstract Current vertebral augmentation procedures (VAPs) often involve devices associated with bone cement leakage. Tripod-Fix is designed to mitigate the risk of bone cement leakage by expanding in three dimensions to fit a narrower vertebral space. This study enrolled 12 patients diagnosed with osteoprorotic vertebral compression fractures (VCFs) for 12 month follow up. The primary outcomes assessed were changes in the Visual Analog Score (VAS) and Oswestry Disability Index (ODI) before and after treatment. Our results demonstrated significant pain relief with VAS decreasing from 8.58 ± 1.83 to 2.75 ± 1.54 cm and improved mobility with ODI decreasing from 73.67 ± 16.29 to 31.83 ± 23.33% post-treatment and sustained for 12 months. Follow-up radiographs revealed no device-related adverse events such as cement leakage, vertebral body collapse, or adjacent vertebral fractures (AVFs). In addition, the mean anterior height restoration ratio after treatment was 15.87 ± 5.13%. Our preliminary findings suggest that Tripod-Fix exhibits safety and efficacy comparable to the third-generation devices currently utilized for treating osteoporotic VCFs.